Long Term Wind Trends Analysis of Coastal Belt of Pakistan - Zeeshan Alam Nayyar; Nayyer Alam Zaigham; Abdul Qadeer (Journal of Basic & Applied Sciences, 2021)
Pakistan has a long coastal belt, stretched over an area of more than 1000 km from Indian border in east to Iranian border in west, which has varying nature of geomorphic, geologic and climatic setups. In view to understand the characteristic nature of the area in relevance to undertake the wind energy assessment study, it is imperative to carry out the time-series climatic analyses especially for the wind parameters. Pakistan coastal belt has its unique windy nature because of the monsoon period in summer and land-to-sea wind behavior in winter, which further varies respect to coastal geomorphologic features. A research study has been conducted to analyze the long term wind speed trends for the salient cities lying near the coast of Pakistan. The seasonal decomposition technique, i.e. multiplicative model, was applied for the wind trend analyses using the wind data of 60 years for five major cities namely Karachi, Badin & Hyderabad in Sindh province and Lasbella & Ormara in Balochistan province. The present study describes the methodology adopted for the calculation of long term wind speed trends and subsequent the results indicate different wind variables of long term time-series analyses for the selected five cities.